Effect of Corn Oil on the Quality Characteristics of Mayonnaise - Ibrahim, Muhammad Suhail; Rasool, Ghulam; Hussain, Sarfraz; Alam, Zafar (Pakistan Journal of Nutrition, 2013)
Mayonnaise is semi-solid stable emulsion of vegetable oil, egg yolk or whole egg, vinegar or lemon juice, salt seasonings and sugars and dextrose. Oil is used in mayonnaise as energy source and for smooth texture. Mayonnaise was prepared by using different concentrations of corn oil (235, 240, 245, 250 and 255 mL). Firstly all the ingredients were weighed by using the electrical balance. Eggs and vinegar was cooled at 10-13°C. After washing and cleaning. Eggs were deshelled.spices and eggs were blended for 2 min. Pouring of oil was started drop by drop at first and then remaining oil was added. Packaging was done in already hygienically cleaned bottles. The product was stores under controllable conditions. During the storage period the product was analyzed for moisture, crude protein, total ash, crude fat,and acidity. The sensory evaluation of the product was also made when stored under controlled conditions. The result of the investigation was statistically analyzed and interpreted. The present project was carried out to study the effect of corn oil on the different quality characteristics of mayonnaise. Different concentrations of corn oil were used to prepare mayonnaise samples. The mayonnaise samples were prepared by using 235, 240, 245, 250 and 255 mL of corn oil. Theses samples were tested for chemical properties like moisture, crude protein, crude fat, total ash, peroxide value and acidity. Among the sensory characteristics it was evaluated for its taste, texture, flavor and overall acceptability during 40 days of storage period. The test was made after 10 days interval up to 40 days. Among chemical characteristics the effect of different oil concentration was non-significant for fat and acidity. While as sensory characteristics were concerned color, flavor, taste, texture and overall acceptability decreased by increasing oil concentration. The last result was shown by the mayonnaise sample prepared by using 235 mL of corn oil. The concentration of 235 mL of corn oil showed good quality attributes especially with respect to its sensory evaluation such as color, taste, texture, flavor and overacceptibility of mayonnaise. Mayonnaise prepared by using 235 mL of corn oil also showed good emulsion stability than others.